2018
DOI: 10.1089/zeb.2018.1596
|View full text |Cite
|
Sign up to set email alerts
|

Partial Dietary Inclusion of Hermetia illucens (Black Soldier Fly) Full-Fat Prepupae in Zebrafish Feed: Biometric, Histological, Biochemical, and Molecular Implications

Abstract: Due to minimal environmental impact, compared to most conventional feed commodities, insects deserve a growing attention as candidate ingredients for aquafeeds. This study tested, for the first time during zebrafish larval rearing, the effects of an increasing replacement (0%-25%-50%) of fish meal by black soldier fly (BSF) full-fat prepupae meal. All diets were formulated to be isonitrogenous and isolipidic. A multidisciplinary approach, including biometrics, histology, gas chromatography-mass spectrometry, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 51 publications
7
53
1
Order By: Relevance
“…No histopathological alterations were observed in the liver of Siberian sturgeons fed HIM based diets. This result is in agreement with those observed in Japanese seabass [29], Atlantic salmon [30,31], zebrafish (Danio rerio) [52], and rainbow trout [16] fed with HIM meal. On the contrary, Li et al [20] observed significant alterations in liver (decrease hepatopancreas fat deposition and increase in mild necrosis and apoptosis of hepatocytes) in Jian carp (Ciprinus carpio var.…”
Section: Histological Investigationssupporting
confidence: 92%
See 1 more Smart Citation
“…No histopathological alterations were observed in the liver of Siberian sturgeons fed HIM based diets. This result is in agreement with those observed in Japanese seabass [29], Atlantic salmon [30,31], zebrafish (Danio rerio) [52], and rainbow trout [16] fed with HIM meal. On the contrary, Li et al [20] observed significant alterations in liver (decrease hepatopancreas fat deposition and increase in mild necrosis and apoptosis of hepatocytes) in Jian carp (Ciprinus carpio var.…”
Section: Histological Investigationssupporting
confidence: 92%
“…One of the limiting factors of including insect meal in fish feed is their chitin content, which is able to determine gut and liver histological changes [16]. In particular, chitin could affect liver lipid accumulation [20] and may induce intestinal inflammation [52]. The histological effects on liver and gut by HIM utilization in diets for different fish species have already been characterized, with different results being obtained until now [16,20,24,31].…”
Section: Histological Investigationsmentioning
confidence: 99%
“…In particular, Truzzi et al (2020) 9 demonstrated that the addition of a 10% (w/w) of Schizochytrium sp. to the growth substrate was an efficient method to enrich BSF final biomass in terms of PUFAs and to increase, with respect to previous studies on zebrafish, the BSF meal inclusion level in the fish diets without affecting fish welfare 21,29,33 . However, the potential of these enriched BSF prepupae as alternative feed ingredient for fish was evaluated only during the fish larval stage 19 .…”
Section: Discussionmentioning
confidence: 77%
“…Importantly, without defatting, it is not easy to use HF larvae in a marine-fish diet and obtain appropriate crude protein and lipid composition, since HF larvae have an excess of crude lipids (20-35%, dry matter) and markedly different fatty acid profiles than feeds made from wild fish. The fatty acid profile in black-soldier fly larvae (Hermetia illucens) was reported to affect lipid composition and accumulation in zebrafish (Danio rerio) [44,45]. Eliminating the hydrophobic faction is, therefore, an important first step in the development of HF larva-based feeds for marine-fish aquaculture.…”
Section: Discussionmentioning
confidence: 99%